Neutrophil Extracellular Traps Activate Proinflammatory Functions of Human Neutrophils - Dömer, Daniel; Walther, Tabea; Möller, Sonja; Behnen, Martina; Laskay, Tamás (Frontiers in Immunology, 2021)
Neutrophil extracellular traps (NETs) consist of decondensed nuclear chromatin that is associated with proteins and are released by neutrophils during an inflammatory response. Released NETs are able to capture pathogens, prevent their dissemination and potentially kill them via antimicrobial peptides and proteins that are associated with the decondensed chromatin. In addition to their antimicrobial functions, NETs have also been shown to exert immunomodulatory effects by activation and differentiation of macrophages, dendritic cells and T cells. However, the effect of NETs on neutrophil functions is poorly understood. Here we report the first comprehensive study regarding the effects of NETs on human primary neutrophils in vitro. NETs were isolated from cultures of PMA-exposed neutrophils. Exposure of neutrophils to isolated NETs resulted in the activation of several neutrophil functions in a concentration-dependent manner. NETs induced exocytosis of granules, the production of reactive oxygen species (ROS) by the NADPH oxidase NOX2, NOX2-dependent NET formation, increased the phagocytosis and killing of microbial pathogens. Furthermore, NETs induced the secretion of the proinflammatory chemokine IL-8 and the B-cell-activating cytokine BAFF. We could show that the NET-induced activation of neutrophils occurs by pathways that involve the phosphorylation of Akt, ERK1/2 and p38. Taken together our results provide further insights into the proinflammatory role of NETs by activating neutrophil effector function and further supports the view that NETs can amplify inflammatory events. On the one hand this amplified functions enhance the antimicrobial defense. On the other hand, NET-amplified neutrophil functions can be involved in the pathophysiology of NET-associated diseases. In addition, NETs can connect the innate and adaptive immune system by inducing the secretion of the B-cell-activating cytokine BAFF.